Pomeroy Sterilization in a Teen with Recurrent Pregnancy and Multiple Cesarean Deliveries: A Case Report - Nurdiawan W; Nisa AS; Susiarno H; Hidayat D; Pusianawati D; Zulvayanti; Ronosulistyo AA; Adriansyah PNA (International Medical Case Reports Journal, 2025)
Windi Nurdiawan, Aisyah Shofiatun Nisa, Hadi Susiarno, Dini Hidayat, Dini Pusianawati, Zulvayanti, Ayu Angelina Ronosulistyo, Putri Nadhira Adinda Adriansyah Department of Obstetric and Gynecology, Faculty of Medicine, Universitas Padjadjaran, Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaCorrespondence: Aisyah Shofiatun Nisa, Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Padjadjaran, Jl. Pasteur No. 38, Bandung, West Java, 40161, Indonesia, Tel +62 821-1572-6914, Email aisyah23009@mail.unpad.ac.idIntroduction: Recurrent teenage pregnancy refers to an adolescent experiencing more than one pregnancy before reaching full adulthood. Pomeroy sterilization in teenagers with a history of two cesarean sections presents a complex issue requiring careful consideration of medical, ethical, and social factors. This case highlights the appropriate management of adolescents in such situations.Case Illustration: An 18-year-old woman, G3P2A0, at full-term pregnancy, presented for elective cesarean section. The patient had no complaints and exhibited no signs of labor at the time of admission. Laboratory findings revealed anemia, with a hemoglobin level of 7.2 g/dL. She received two units of packed red cell (PRC) transfusions preoperatively. A cesarean section was performed, delivering a healthy baby boy weighing 2720 grams and measuring 47 cm. After a thorough discussion and informed consent regarding contraceptive options, the patient and her husband opted for Pomeroy sterilization, as they felt their family was complete.Conclusion: Managing teenage pregnancy requires a holistic and cautious approach, especially in cases involving previous cesarean sections. Comprehensive care, including monitoring for complications such as anemia and fetal growth restriction, is essential for ensuring maternal and neonatal health. Furthermore, informed decision-making regarding contraception is vital to prevent recurrent pregnancies and support the psychosocial well-being of adolescent mothers. This approach helps achieve better outcomes for both mother and child.Keywords: anemia, fetal growth restriction, Pomeroy sterilization, recurrent teenage pregnancy